2012
DOI: 10.1021/nn2042016
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Analysis of Lipid Vesicles Encapsulating Hydrophobic Gold Nanoparticles

Abstract: The structure and stability of hybrid lipid vesicles containing bilayer-encapsulated hydrophobic nanoparticles is dependent upon lipid phase behavior. By embedding stearylamine-stabilized gold nanoparticles in dipalmitoylphosphatidylcholine/dipalmitoylphosphatidylglycerol vesicles, we show that encapsulation at lipid to nanoparticle ratios from 10,000:1 to 5000:1 leads to bilayer thickening and hydrophobic mismatch, favoring nanoparticle inclusion in gel phase vesicles. High loadings lead to large increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 47 publications
(79 reference statements)
4
76
0
Order By: Relevance
“…In addition, removal of free metal nanoparticles (that is, metal nanoparticles that are not encapsulated) and free liposomes (that is, liposomes that do not contain metal nanoparticles) must be done carefully through additional separations ( 25 27 ). On the other hand, metal nanoparticles can also be embedded between lipid bilayers or, alternatively, can be attached to the outer liposome surface through delicate control of their surface chemistry ( 21 , 23 , 28 30 ). However, for both methods, the metal nanoparticles should be small enough to produce a stable hybrid structure without degrading the structural integrity of the lipid bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, removal of free metal nanoparticles (that is, metal nanoparticles that are not encapsulated) and free liposomes (that is, liposomes that do not contain metal nanoparticles) must be done carefully through additional separations ( 25 27 ). On the other hand, metal nanoparticles can also be embedded between lipid bilayers or, alternatively, can be attached to the outer liposome surface through delicate control of their surface chemistry ( 21 , 23 , 28 30 ). However, for both methods, the metal nanoparticles should be small enough to produce a stable hybrid structure without degrading the structural integrity of the lipid bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…A change in lipid ordering should also affect the phase transition, but no significant change in the T m of liposome bilayers was observed after incorporating palmityl-nitroDOPA stabilized 5 nm core diameter iron oxide nanoparticles in the liposome membranes [21]. Relatively disperse sterylamine coated nanoparticles in LUVs were also reported by Bothun et al [24]. They further reported effects on lipid organization and T m that was depended on nanoparticlelipid ratio.…”
Section: Nanoparticles Incorporated In the Membranementioning
confidence: 71%
“…Magnetically responsive nanoparticles can be as small as a few nanometer in diameter [10] and can therefore be encapsulated into the nanoscale structures of drug delivery vehicles. Nanoparticles of such small size even allows for inclusion in the lipid membranes of liposomes [21][22][23][24]. As mentioned, an efficient permeability barrier that can be modified for use in vesicular drug delivery vehicles is the cell mimetic membrane which has a hydrophobic membrane core surrounded by hydrophilic faces; drug delivery liposomes are smaller than 100 nm and comprise synthetic or natural lipids (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, precise characterization of these highly complex constructs is not straightforward. Von White G 2nd et al just recently demonstrated the impact of nanoparticles encapsulated in the liposomal membrane on its transition phase temperature (Tm) [22]. Standard characterization techniques,…”
mentioning
confidence: 99%